The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s11739-017-1762-1
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobin concentration is associated with self-reported disability and reduced physical performance in a community dwelling population of nonagenarians: the Mugello Study

Abstract: People aged 90 and older represent a fast-growing population segment who deserve specific attention and research. Aging is associated with a progressive decrease in hemoglobin concentration, which predicts adverse outcome, such as mortality, morbidity, frailty and disability. Whether this association is independent from increased prevalence of comorbidity, causing both anemia and reduced physical function is yet under debate. The aim of this study is to explore the relationship between hemoglobin concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 33 publications
(50 reference statements)
4
15
0
Order By: Relevance
“…According to a previous study, resistance exercise improved hemoglobin status by increasing heme synthesis in the bone marrow in moderately iron-deficient rats (36), which could decrease the risk of anemia among the older elderly. A previous study reported that blood hemoglobin level was associated with physical performance in the community-dwelling elderly, similar to our result (37).…”
Section: Discussionsupporting
confidence: 93%
“…According to a previous study, resistance exercise improved hemoglobin status by increasing heme synthesis in the bone marrow in moderately iron-deficient rats (36), which could decrease the risk of anemia among the older elderly. A previous study reported that blood hemoglobin level was associated with physical performance in the community-dwelling elderly, similar to our result (37).…”
Section: Discussionsupporting
confidence: 93%
“…This study also confirms that the effect of anemia on the occurrence of low HGS is independent of other sociodemographic, anthropometric, and clinical factors [28]. Although a possible link between reduced HGS and the multiple etiological factors of anemia beyond the scope of the present study is recognized, a plausible explanation for the findings is that the reduction of hemoglobin levels decreases the oxygen consumption capacity of the muscles, leading to tissue hypoxia that promotes the decline of physiological reserve [29].…”
Section: Discussionsupporting
confidence: 86%
“…In the current study, the level of hemoglobin and ferritin decreased with age, and in particular in the nursing home residents caused by several reasons, including reduced erythropoietin secretion, reduced hematopoietic reserve, decreased intake of iron and vitamins, and the chronic illnesses that occur with chronic inflammatory diseases (30). The results of the current study were consistent with those of other studies (3,4,9,13,15,29,31,33).…”
Section: Discussionsupporting
confidence: 91%